Description of Skin Anatomical Structures of Wistar Rats Exposed to X-Rays Radiation - Lisdiana -; Agus Ernawati (Biosaintifika: Journal of Biology & Biology Education, 2015)
The research was aimed to find out a profile of an anatomical structure of the Rattus norvegicus skin after exposed to X-ray radiation. Research was performed by treating the 20 Rattus norvegicus at the age of 1.5 months. The weight rats were weighed approximately 100 ± 13 g grouped into four treatments with different dose of X-ray radiation. The four treatments were 0 mgy (control), 50 mgy, 100 mgy, and 150 mgy X-ray radiation. The variable in this research was a dose of X-ray radiation and the anatomical structure of the rattus norvegicus skin. The data obtained were analyzed with qualitative description. The research results after exposure of X-ray radiation for 5-days showed that there was no damage on the skin macroanatomy. Whereas, the observation in the skin microanatomy showed that there was a damage, e.g. thinning of the epidermis, cell picnosys, cell injury, and hemoragic. The result indicated that the different dose of X-ray radiation affected the skin anatomy structure. The X-ray radiation exposure at 100 mGy on skin microanatomy were caused a thinning of the epidermis in stratum corneum layer, picnosys on the nucleus, cell injury and hemoragic.Penelitian ini bertujuan untuk mengetahui gambaran struktur anatomi kulit tikus (Rattus norvegicu) strain Wistar setelah terpapar radiasi sinar-X. Sebanyak 20 ekor tikus umur 1,5 bulan dengan berat badan sekitar 100 ± 13 gram dikelompokkan ke dalam 4 perlakuan yaitu perlakuan dosis radiasi sinar-X sebesar 50 mGy, 100 mGy dan 150 mGy serta 1 kelompok kontrol. Paparan radiasi dilakukan selama 5 hari. Variabel penelitian ini adalah dosis paparan radiasi sinar-X dan struktur anatomi kulit. Data yang diperoleh dianalisis secara deskriptif kualitatif. Hasil penelitian menunjukkan bahwa secara makroanatomi kulit tikus tidak terlihat kerusakan, tetapi secara mikroanatomi terdapat kerusakan berupa penipisan epidermis, piknosis sel, jejas sel, dan hemoragik. Hal tersebut dikarenakan besarnya dosis radiasi mempengaruhi terhadap perubahan struktur anatomi kulit. Paparan radiasi sinar-X dosis 100 mGy, menimbulkan kerusakan kulit tikus secara mikroanatomi berupa penipisan epidermis dilapisan stratum korneum, piknosis inti, jejas sel dan hemoragik.